Why Nations Go to War - Stoessinger, John G. (New York St. Martin's Press, 1990)
Provides seven detailed case studies which focus on the fateful moment when leaders crossed the threshold which made armed conflict inevitable. The fifth edition covers the end of the Iran-Iraq war, the Palestinian "Intifada" and the impact of the arrival of Gorbachev on the international scene.
Keywords: History, Modern -- War